Fatigue as a Cause of Professional Dissatisfaction Among Chinese Nurses in Intensive Care Unit During COVID-19 Pandemic - Sun T; Huang XH; Zhang SE; Yin HY; Li QL; Gao L; Li Y; Li L; Cao B; Yang JH; Liu B (Dove Medical Press, 2023)
Tao Sun,1,* Xian-Hong Huang,1,* Shu-E Zhang,2,* Hong-Yan Yin,3 Qing-Lin Li,2 Lei Gao,2 Ye Li,2 Li Li,4 Bing Cao,5 Jin-Hong Yang,6 Bei Liu7 1Department of Health Policy and Management, School of Public Health, Hangzhou Normal University, Hangzhou, 311121, People's Republic of China; 2Department of Health Management, School of Health Management, Harbin Medical University, Harbin, 150081, People's Republic of China; 3Department of Humanities and Social Sciences, Harbin Medical University (Daqing), Daqing, 163319, People's Republic of China; 4Department of Administration, School of Law, Zhejiang University City College, Hangzhou, 310015, People's Republic of China; 5Department of Oncology, Weifang People's Hospital, Weifang, 261000, People's Republic of China; 6Key Laboratory of Cognition and Personality, Faculty of Psychology, Ministry of Education, Southwest University, Chongqing, 400715, People's Republic of China; 7Global Center for Infectious Disease and Policy Research, Peking University, Beijing, 100191, People's Republic of China*These authors contributed equally to this workCorrespondence: Bei Liu, Global Center for Infectious Disease and Policy Research, Peking University, Beijing, 100191, People's Republic of China, Email 18827380717@163.comAim: To clarify the mediating role of burnout and the moderating role of turnover intention in the association between fatigue and job satisfaction among Chinese nurses in intensive care units (ICU) during the COVID-19 pandemic.Methods: A cross-sectional survey of fifteen provinces in China was conducted, using an online questionnaire, from December 2020 to January 2021, during the COVID-19 pandemic. A total of 374 ICU nurses (effective response rate: 71.37%) provided sufficient responses. Sociodemographic factors, job demographic factors, fatigue, burnout, job satisfaction, and turnover intention were assessed using questionnaires. General linear modeling (GLM), hierarchical linear regression (HLR) analysis, and generalized additive modeling (GAM) were performed to examine all the considered research hypotheses.Results: Fatigue was found to be negatively and significantly associated with job satisfaction. Moreover, burnout played a partial mediating role and turnover intention played a moderating role in the relationship between fatigue and job satisfaction.Conclusion: Over time, a state of physical and mental exhaustion and work weariness among Chinese ICU nurses potentially results in job burnout and consequently promotes the level of job dissatisfaction. The results also found that turnover intention played a moderating role in the relationship between burnout and job satisfaction. Specific policies could be considered to eliminate nurses' fatigue and negative attitudes during times of public health emergencies.Keywords: ICU nurses, fatigue, burnout, job satisfaction, turnover intention, COVID-19 pandemic